2009
DOI: 10.1007/s10681-009-9935-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide QTL analysis for pre-harvest sprouting tolerance in bread wheat

Abstract: A framework linkage map comprising 214 molecular marker (SSR, AFLP, SAMPL) loci was prepared using an intervarietal recombinant inbred line (RIL) mapping population of bread wheat. The RIL population that was developed from the cross SPR8198 (red-grained and PHS tolerant genotype) 9 HD2329 (white-grained and PHS susceptible genotype) following single seed descent segregated for pre-harvest sprouting (PHS). The RIL population and parental genotypes were evaluated in six different environments and the data on PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 50 publications
8
54
1
Order By: Relevance
“…The continuous normal and skewed distributions of the population indicated that multiple minor alleles are involved in controlling seed dormancy. This complex genetic control of dormancy is consistent with earlier studies Kulwal et al 2004;Imtiaz et al 2008;Mohan et al 2009;Fofana et al 2009). The f Positive sign in germination resistance (GR) and negative sign in germination index (GI) and in percent germination (PG) indicated that SC8021-V2 allele contributed resistance for respective trait measure-duration relative to the AC Karma allele (values given in range for respective trait measure with multiple durations) g QTL designation (favourable parental allele) different durations of germination maximized differential under some conditions, revealing a bimodal distribution that indicated, in addition to minor genes, the presence of a major gene.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The continuous normal and skewed distributions of the population indicated that multiple minor alleles are involved in controlling seed dormancy. This complex genetic control of dormancy is consistent with earlier studies Kulwal et al 2004;Imtiaz et al 2008;Mohan et al 2009;Fofana et al 2009). The f Positive sign in germination resistance (GR) and negative sign in germination index (GI) and in percent germination (PG) indicated that SC8021-V2 allele contributed resistance for respective trait measure-duration relative to the AC Karma allele (values given in range for respective trait measure with multiple durations) g QTL designation (favourable parental allele) different durations of germination maximized differential under some conditions, revealing a bimodal distribution that indicated, in addition to minor genes, the presence of a major gene.…”
Section: Discussionsupporting
confidence: 92%
“…QTL, QPhs.spa-2A, for GI7d from the GH environment was in interval gwm294-cfa2058 on chromosome 2A, a different position from the previous reports (Mohan et al 2009;Kumar et al 2009;Kobayashi et al 2010;Jaiswal et al 2012;Knox et al 2012). The marker coverage was low on chromosome 2A which may affect the QTL position and this conclusion.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations